THE INFLUENCE OF FINANCIAL RATIOS ON BOND RATINGS OF BANKING COMPANIES IN 2019-2023 - Alindra Yanuardi; Novia Afifatur Rohmah (CV. Lafadz Jaya, 2026)
The downgrade of bond ratings by PT PEFINDO amidst the COVID-19 outbreak was the driving force behind this study. It can be seen from the downgrade of the bond ratings of these companies, which indicates that the risk of default is increasing. Theoretically, several factors, including financial ratios, can influence bond ratings. The purpose of this study was to examine the impact of LDR, BOPO, ROA, and CAR on the bond ratings of banking companies assessed by PT PEFINDO from 2019 to 2023. The sampling technique used was purposive sampling. The data analysis method used was ordinal logistic regression analysis, performed using the SPSS 26 program. Based on the study's results, bond ratings were significantly influenced simultaneously by LDR, BOPO, ROA, and CAR. LDR has a positive and significant effect, and BOPO has a negative and significant effect. ROA and CAR do not have a significant effect on bond ratings.